Implementation of project based learning "Village Environment Bigbook" for early childhood - Wiijati, Aris Yuliana; Rodtian, Abeedah (Thufuli, 2025)
This research aims to examine the implementation of the project-based learning model within the institution and to analyze the understanding in accordance with Hurclok's theory. This study aims to assess the effectiveness of Project-Based Learning (PjBL) in enhancing children's reasoning and understanding of their environment. This study employs a qualitative case study approach as outlined by Miles and Huberman, focusing on the implementation of project-based learning titled "bigbook of the village environment." The techniques employed for data collection consist of observation, interviews, and documentation. Observations were carried out throughout the learning process, interviews were held with teachers and the school principal, and documentation was utilized to enhance data collection. The data analysis techniques utilized triangulated various data sources. This research indicates that teachers implement Project-Based Learning (PJBL) through six steps: 1) reviewing the current theme, 2) grouping students, 3) implementation, 4) monitoring, 5) assessment, and 6) evaluation. PjBL can promote children's development and improve understanding, as articulated by Hurlock.